The Other Half of Gender : Men's Issues in Development. - Correia, Maria; Bannon, Ian (World Bank Group, 2006)
This book is an attempt to bring the gender and development debate full circle--from a much-needed focus on empowering women to a more comprehensive gender framework that considers gender as a system that affects both women and men. The chapters in this book explore definitions of masculinity and male identities in a variety of social contexts, drawing from experiences in Latin America, the Caribbean and sub-Saharan Africa. It draws on a slowly emerging realization that attaining the vision of gender equality will be difficult, if not impossible, without changing the ways in which masculinities are defined and acted upon. Although changing male gender norms will be a difficult and slow process, we must begin by understanding how versions of masculinities are defined and acted upon.